Design And Development of a Vehicle Security System Using Vibration Sensors and GPS Based on Arduino - Gunawan; Achmad Yani; Junaidi; Zumhari; E Hutajulu; R Sirait (Yayasan Sinergi Multidimensi Kreatif, 2024)
Incidents of theft and theft of motor vehicles have recently become more and more prevalent. This is suspected by the increase in the number of motorized vehicles every year. The most stolen or stolen types of motor vehicles are two-wheeled vehicles or motorcycles. So the researcher in this case conducted research in the form of designing motor vehicle safety using brittle sensors and GPS (Global Positioning System). The vibration sensor is functional to detect theft by forcibly moving the vehicle. Meanwhile, GPS functions to detect the location of the presence of the motor vehicle so that it can be monitored by the owner of the vehicle. This research focuses on measuring the accuracy and optimization of vibration sensors and GPS so that outputs in the form of simple patents and prototypes of motor vehicle safety devices can be obtained.